Shop Floor Management in the Era of Digitalization: Systematic Literature Review - Eva JELINKOVA; Petra TAUSL PROCHAZKOVA (Communications of International Proceedings, 2022)
Digitalization and the concept of Industry 4.0 are fundamental topics currently resounding in the real entrepreneurial world and academic sphere. They have a vital impact on the present functioning of entrepreneurial entities and challenge them to make radical changes in the management of business processes and their activities. Shop Floor Management is one of the key managerial approaches of lean production and its positive impact on firm performance and the effectiveness of the manufacturing process has been supported by multiple works of research. The goal of this paper is to systematically map the field of Shop Floor Management. The study especially aims to map its primary thematic areas and confirm the assumption that one of the main fields is that of digitalization. Based upon systematic literature review, the main thematic areas of Shop Floor Management and their future research activities are presented. Three main areas of future research activities have been defined: the field of digitalization itself, the level of Shop Floor Management implementation, and the third area, which involves focusing on one of the most demanding business processes – the process of production planning, specifically the scheduling of manufacturing operations. Findings that point to the need for research activities in the area of small and medium sized enterprises add an additional dimension to the completed research.
Keywords: shop floor management; digitalization; lean; production; Industry 4.0.